Catalytic Activity for CO2 Hydrogenation is Linearly Dependent on Generated Oxygen Vacancies over CeO2‐Supported Pd Catalysts. Issue 16 (13th June 2022) - Jiang, Feng; Jiang, Feng; Wang, Shanshan; Xu, Yuebing; Liu, Bing; Liu, Xiaohao
Abstract: CO2 hydrogenation to methanol is a promising way to achieve the utilization of CO2 to high‐value chemicals. Promoters are frequently applied to regulate the chemical and physical properties of catalysts, but their critical role in selective CO2 hydrogenation toward methanol over Pd/CeO2 is still far from clear. In this work, a series of promoters including La, Zr, Cr, Ca, Co, Cd, Zn, Bi, and K are selected to co‐impregnate with Pd precursor on ceria nanorods to reveal their impact on CO2 hydrogenation performance. It turns out that the catalytic activity over Pd/CeO2 catalyst is linearly dependent of the amount of created oxygen vacancies which determines by the nature of promoter. Especially, the introduction of Zr could incorporate into ceria lattice for the facile formation of oxygen vacancies, thus notably enhancing the catalytic activity with slightly higher methanol selectivity. Abstract : CO2 to methanol : The incorporation of Zr promoter into ceria lattice results in the creating of more oxygen vacancies and more dispersed Pd species, which enhances catalytic activity and methanol selectivity in carbon dioxide hydrogenation.